2019
DOI: 10.3390/sports7100214
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring-to-Quadriceps Ratio in Female Athletes with a Previous Hamstring Injury, Anterior Cruciate Ligament Reconstruction, and Controls

Abstract: Muscle strength imbalances around the knee are often observed in athletes after anterior cruciate ligament (ACL) surgery and hamstring muscle injury. This study examined three hamstrings-to-quadriceps (H:Q) strength ratio types (conventional, functional, and mixed) in thirteen female athletes with a history of hamstring injury, fourteen basketball players following ACL reconstruction and 34 controls. The conventional (concentric H:Q) peak torque ratio was evaluated at 120°·s−1 and 240°·s−1. The functional (ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…For example, peak torque values of the extensors and flexors occur at different knee joint flexion angles [ 64 ]. Hence, many authors are considering refining this predictor or providing alternative variants (e.g., functional H/Q ratio) so that the disproportions between antagonistic muscle groups can be better assessed [ 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, peak torque values of the extensors and flexors occur at different knee joint flexion angles [ 64 ]. Hence, many authors are considering refining this predictor or providing alternative variants (e.g., functional H/Q ratio) so that the disproportions between antagonistic muscle groups can be better assessed [ 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fujita et al [21] and Kellis et al [22] included only female participants in their studies. However, a few other studies [19,20] recruited both genders.…”
Section: Discussionmentioning
confidence: 99%
“…These results contradict those of a few previous studies. According to a few recent studies [21,22], the muscle strength ratio of the flexor and extensor muscles in the knee does not affect the risk of knee pain and sports injury. This difference is attributed to the biomechanical differences in structure between men and women [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during a sprint, a reduced eccentric strength may be responsible for hamstring injury and not a lack of flexibility. Several studies showed that the occurrence of hamstring injuries can be caused by eccentric hamstring weakness, muscle imbalance of the limb (eg, dominant side and non‐dominant side), imbalance of the hamstring‐to‐quadriceps ratio (=parameter to estimate muscle strength balance between the agonist and antagonist), and hamstring flexibility 34,35 . In addition to this biomechanical aspect, the SRT is not consistent with the sport context.…”
Section: Discussionmentioning
confidence: 99%